3D CT/MRI fusion image-assisted treatment of lumbar burst fractures with laminar fractures - Zhenhui Zhang; Qiangqiang Pan; Qingde Wang; Wei Mei; Xuyi Chen (BMC Musculoskeletal Disorders)
Abstract Background Lumbar burst fracture combined with lamina fracture is a special type of spinal fracture. Neither CT nor MRI can accurately determine it. The present study aims to investigate the clinical value of 3D CT/MRI fusion imaging in the treatment of lumbar burst fracture complicated with lamina fracture. Methods The clinical data of 38 patients with lumbar burst fracture combined with lamina fracture admitted to our hospital from January 2015 to December 2020 were retrospectively analyzed. CT and MRI examinations were performed before surgery, and the 3D fusion images of CT and MRI were reconstructed by Medraw software to determine whether lumbar burst fractures with interlaminar herniation of the cauda equine and entrapped nerve root. The American Spinal Injury Association (ASIA) scale was used to evaluate neurological function before and after surgery. Results All patients underwent posterior lumbar decompression and fusion. Among them, 30 (78.9%) patients had a dural hernia of the cauda equina. The follow-up time was (17.8 ± 1.6) months, the average operative time was 115.6 min (85–162 min), and the mean blood loss was 185.3 mL (136–240 mL). At the last follow-up, ASIA scale of neurological function was as follows: 5 cases were grade C, eight were grade D, and twenty-five were grade E. The difference was statistically significant compared with that before the operation (P < 0.05). Delayed wound healing occurred in 2 patients after surgery, and they were cured after systematic treatment. Conclusions The 3D CT/MRI fusion imaging can accurately and intuitively construct the position relationship of the dura mater, cauda equina and the posterior fractured lamina, which can guide the formulation of a surgical plan and determine the range of nerve decompression. Clinical trial number Not applicable.